Instrumental music therapy reduced depression levels in stroke patients - Vione Deisi Oktavina Sumakul; Hari Basuki Notobroto; Ni Luh Widani; M. Havidz Aima (SAGE Publishing, 2020)
Background: Stroke is the fifth cause of death and disability, leading also to depression. However, depression in stroke patients is hardly handled optimally. The purpose of this study therefore is to determine the effectiveness of instrumental music therapy in reducing depressive symptoms in stroke patients. Design and methods: It used a quasi-experiment pre-post design with a simple random sampling with 59 respondents. The respondents were divided into 3 groups as follows; group A (standard treatment), group B (instrumental music therapy), and group C (combined treatment). Results: The results show that the combined treatment provided the most significant influence on reducing the level of depression (P=0.001) with a contribution of 68.6% compared to the group A which was given standard treatment (P=0.001) with a contribution of 61.7%. Instrumental music therapy had no effect (P=0.986), though it contributed most among the three interventions, specifically 82.6%. Conclusions: The study recommended further improvement to include music as treatment options for reducing depression among stroke patients.